Linking the tropical Northern Hemisphere pattern to the pacific warm blob and Atlantic cold blob - Liang, YC; Yu, JY; Saltzman, ES; Wang, F (eScholarship, University of California, 2017)
During 2013-15, prolonged near-surface warming in the northeastern Pacific was observed and has been referred to as the Pacific warm blob. Here, statistical analyses are conducted to show that the generation of the Pacific blob is closely related to the tropical Northern Hemisphere (TNH) pattern in the atmosphere. When the TNH pattern stays in its positive phase for extended periods of time, it generates prolonged blob events primarily through anomalies in surface heat fluxes and secondarily through anomalies in wind-induced ocean advection. Five prolonged (≥24 months) blob events are identified during the past six decades (1948-2015), and the TNH-blob relationship can be recognized in all of them. Although the Pacific decadal oscillation and El Niño can also induce an arc-shaped warming pattern near the Pacific blob region, they are not responsible for the generation of Pacific blob events. The essential feature of Pacific blob generation is the TNH-forced Gulf of Alaska warming pattern. This study also finds that the atmospheric circulation anomalies associated with the TNH pattern in the North Atlantic can induce SST variability akin to the so-called Atlantic cold blob, also through anomalies in surface heat fluxes and wind-induced ocean advection. As a result, the TNH pattern serves as an atmospheric conducting pattern that connects some of the Pacific warm blob and Atlantic cold blob events. This conducting mechanism has not previously been explored.